Conceptual design model of interactive television advertising: Towards influencing impulse purchase tendency - Che Omar, Azizah; Shiratuddin, Norshuhada; Sarif, Siti Mahfuzah (Asian Research Publishing Network (ARPN), 2015)
Various studies have proposed factors of impulse purchase in different advertising mediums like website, mobile, traditional retail store and traditional television.However, to the best of the researchers’ knowledge, none of the impulse purchase model is dedicated towards impulse purchase tendency for interactive TV (iTV) advertising.In addition, through systematic review analysis, this study discovered that all the previous models did not emphasize on the conceptual design model of iTV advertising. Therefore, based on a comparative analysis, this study looked for the components in order to propose a conceptual design model of interactive television advertising toward impulse purchase (iTVAdIP).It is suggested that components of the proposed model is classified classify into three categories; layer of technology, development process and impulse purchase components.These categories are represented through a figure for a better clarity.